Research on compressed air energy storage systems using cascade phase-change technology for matching fluctuating wind power generation - Wang, Kangxiang; Chen, Laijun; Li, Xiaozhu; Zhu, Chuang (Frontiers in Energy Research, 2024)
The wind speed varies randomly over a wide range, causing the output wind power to fluctuate in large amplitude. An isobaric adiabatic compressed air energy storage system using a cascade of phase-change materials (CPCM-IA-CAES) is proposed to cope with the problem of large fluctuations in wind farm output power. When the input power is lower than the minimum energy storage power of the compressor, the gradient phase-change thermal energy storage is utilized to broaden the operating range of the system. Second, the system design method and operation rules are elaborated. The storage/release characteristic curve is obtained by constructing the system components and the overall variable operating condition model. A matching system scheme is designed according to the characteristics of a wind farm in a port in China. The case study shows that the wind farm configured with the CPCM-IA-CAES system reduces the wind abandonment rate by 5.7%, recovers 4,644.46 kW h of wind power abandonment, and improves the storage power index by 16.67% compared with that of IA-CAES. Meanwhile, the system efficiency is increased from 65.96% to 74.68%, and the energy storage density is increased from 8.69 to 9.89 kW h m−3.